All about Corduroy - Freeman, Don 1908-1978. (New York Viking Press, 1978)
Story 1:A toy bear in a department store wants a number of things, but when a little girl finally buys him he finds what he has always wanted most of all. Story 2: About a toy bear who wants a pocket for himself and searches for one when he is left behind in the laundromat.
Keywords: orduroy (Fictitious character) -- Juvenile fiction; Teddy bears -- Juvenile fiction; Corduroy